Diplomatic relations and cross-border investments in the European Union - Giacomo Damioli; Wildmer Daniel Gregori (Publications Office of the European Union, 2021)
This study investigates the extent to which diplomatic relations affected merger and acquisition (M&A) activities in the European Union during the years 2001- 2019. Implementing a gravity model, we find a U-inverted relationship between diplomatic distance and M&A activities: (i) a worsening in diplomatic relations fosters M&As, but beyond a certain level (ii) an increase in diplomatic distance slows down M&A flows. While (ii) is in line with the dominant evidence found in the literature on political relations and foreign direct investments, (i) suggests that cross-border acquisitions, as supported by the internalisation theory, are a way for the investing firm to mitigate weak diplomatic relations' related issues, such as access to host markets' information and technology. These findings are confirmed especially when foreign investors target technology-intensive firms, as well as in the most recent years.
Keywords: F21; F52; G34; P16; 330; Diplomatic relations; Cross-border M&A; EU; Foreign location choices; Gravity model